1996
DOI: 10.1164/ajrccm.154.2.8756798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution on the respiratory health of asthmatic children living in Mexico City.

Abstract: The relation between air pollution and the exacerbation of childhood asthma was studied in a panel of 71 children (aged 5 to 7 yr) with mild asthma who resided in the northern part of mexico City. During the follow-up, ambient measures of particulate matter less than 10 microns (PM10, 24-h average) and ozone (1-h maximum) frequently exceeded the Mexican standards for these contaminants. The peak expiratory flow rate (PEFR) was strongly associated with PM10 levels and marginally with ozone levels. Respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
185
4
17

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(213 citation statements)
references
References 0 publications
7
185
4
17
Order By: Relevance
“…Health effects attributed to the presence of fine and coarse particulates have been studied previously in Mexico City (Castillejos et al, 1992(Castillejos et al, , 1995Romieu et al, 1996Romieu et al, , 1997Romieu et al, , 2002aHolguin-Molina et al, 2003;Loomis and Kromhout, 2004); however, these studies did not take into account personal exposure assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Health effects attributed to the presence of fine and coarse particulates have been studied previously in Mexico City (Castillejos et al, 1992(Castillejos et al, , 1995Romieu et al, 1996Romieu et al, , 1997Romieu et al, , 2002aHolguin-Molina et al, 2003;Loomis and Kromhout, 2004); however, these studies did not take into account personal exposure assessment.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another panel study of children in the Netherlands found that only the group with bronchial hyperresponsiveness and relatively high concentrations of serum total IgE appeared susceptible to air pollution. 19 These observations suggest interactive effects between air pollutants and allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to evaluate whether interactions with allergens also played a role in these effects as relevant data were not reported. There is some evidence that exposure to the smaller fraction of particulate matter (PM2.5), may be more important than that to PM10 for acute respiratory symptoms [23] and even for death from respiratory diseases [24]. Unvented domestic gas appliances may contribute to NO 2 exposure [25].…”
Section: Discussionmentioning
confidence: 99%